Farmers' perceptions on varietal diversity, trait preferences and diversity management of bush yam ( Dioscorea praehensilis Benth.) in Ghana - Adewumi, A.S.; Asare, P.A.; Adu, M.O.; Taah, K.J.; Akaba, S.; Mondo, J.; Agre, A.P. (Elsevier, 2021)
Bush yam (Dioscorea praehensilis Benth.) is an important food and cash crop species in some West and Central African countries. Unfortunately, several socioeconomic, cultural, nutritional, and agronomic constraints hinder its cultivation, and thus lead to its underutilization and gradual disappearance. To effectively promote its cultivation and utilization, knowledge of its diversity, distribution, management, and farmers’ varietal preferences is necessary. This study, therefore, used a participatory rural appraisal survey to assess such information in 23 villages from three regions of Ghana. A total of 42 D. praehensilis morphotypes were recorded and grouped in seven classes based on the tuber flesh colour. The Shannon diversity index (H’ = 1.88), equitability (0.65), and Margalef species richness (2.53) revealed the presence of moderate diversity and distribution in the surveyed regions. Farmers’ variety trait preferences included mainly the early maturity (21.1%), smooth tuber texture (16.5%), stability in tuber flesh colour (7.86%), good storage aptitude (7.6%), and high tuber productivity (12.8%). In contrast, D. praehensilis production and utilization rates have declined mainly due to poor culinary quality (39.9%) and poor agronomic traits (20.7%) of most morphotypes. Survey results showed that D. praehensilis is largely an in-situ conserved species in Ghana (60.0%). This study provided an insight on D. praehensilis diversity, distribution and farmers’ varietal preferences in Ghana which will guide its genetic resource conservation and plant breeding interventions.